Learning by teaching: developing transferable skills - Stollhans, Sascha (Research-publishing.net, 2016)
Learning by teaching (German: Lernen durch Lehren, commonly abbreviated as LdL) is a teaching and learning approach which was developed by the French language teacher Jean-Pol Martin in German schools in the 1980s (Martin, 1985). The method sees students in the role of the teacher, and enhances their learning experience by encouraging them to teach other students and collaborate with fellow learners. This case study presents an ongoing project in which second year students of German at the University of Nottingham plan, design and deliver a teaching session for first year beginners’ students. The sessions are either carried out face-to-face or via video tutorials. This is an opportunity for the ‘student teachers’ to apply the knowledge they have acquired within the linguistics module Fremdsprachen lernen und lehren (‘learning and teaching foreign languages’) in a real-life context and to consolidate their own knowledge of German. The first year students, on the other hand, benefit from their peers’ experience, knowledge and enthusiasm. By working on their projects, students have the opportunity to develop a number of transferable skills, such as teamwork, presentation and communication skills, and creativity.